"Kuźnia socjalizmu". Biblioteka we wsi Płoty w województwie zielonogórskim w latach 1950-1956 = "The Forge of socialism". The Płoty village library in the Zielona Góra region, in the years 1950-1956 - Koteluk, Daniel (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The library in Płoty was established in 1950. Until 1955, it was managed by Tatiana Girdwojn. In 1952, the library collection consisted of 1450 books. It wa sdominated by ideological works unequivocally idealizing the Polish and Soviet state, as well as their communist leaders. In addition, they called for an uncritical engagement in collectivization, whose underlying purpose was to enable the State to incapacitate farmers economically, as with other workers. In favorable conditions, i.e., following the rise to power of the country?s new leadership of the Polish United Workers? Party, a cooperative production unit in Płoty was liquidated. It is interesting that at the end of 1956, the local library was closed down. It was re-opened in March 1957.
Keywords: biblioteki; biblioteki wiejskie; Płoty (woj. lubuskie, pow. zielonogórski, gm. Czerwieńsk); socjalizm; propaganda; libraries; rural libraries; socialism